System zaopatrzenia w wodę miasta Nowa Sól = Water supply system in Nowa Sol - Ogiołda, Ewa; Gajda, Marta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Characteristics of water supply system in Nowa Sol including its elements and water consumption have been presented. The results make it possible to compare with exploited system parameters. Hydraulic model could be used to carry out the simulation calculations.
Keywords: zużycie wody; obliczenia hydrauliczne; system zaopatrzenia w wodę; water consumption; hydraulic calculations; water supply system